EPISTEMOLOGICAL OBSTACLE SISWA SMA DALAM MATERI TURUNAN TRIGONOMETRI - Laili Rahmawati; Kintan Tyara Augie; Nanang Priatna (IKIP Siliwangi, 2021)
The learning system that was originally carried out at school became a long distance learning system at home which resulted in changes to student learning outcomes, especially in the derivative of trigonometic function. Students' limitations in understanding about derivative of trigonometric function became students’ learning obstacle during the pandemic. This study aims to analyze the epistemological obstacle of high school students in the derivative of trigonometric function during the pandemic. This study use qualitative method with case study design. The subjects of this study were 23 students of grade XII of Senior High School in Cirebon City and Garut Regency. Data collected by using test and semi-structured interview. Technical analysis of data using data reduction, data presentation and conclusion drawing. The results showed that students experienced an Epistemological Obstacle related to solving derivative problems of trigonometric functions, seen from students' errors in deriving basic trigonometric functions, derivatives in the form of multiplication, chain derivatives and derivatives involving mixed algebraic and trigonometric forms as well as errors in determining derivatives at a certain point.